Characterization of the novel HLA‐A*11:376 allele by sequencing‐based typing. (5th January 2021) - Elsermans, Vincent; Visentin, Jonathan; Top, Isabelle; Varlet, Pauline; Labalette, Myriam
Abstract : HLA‐A*11:376 differs from HLA‐A*11:01:01:01 by one nucleotide substitution in codon 168 in exon 3.